Development of Pythagorean Neutrosophic Hypersoft Set with Application in Work Life Balance Problem - Saeed, Muhammad; Ashraf, Mobeen; Ijaz, Aleen; Jaffar, Muhammad Naveed (HyperSoft Set Methods in Engineering, 2024)
By introducing Pythagorean Neutrosophic Hypersoft Sets and giving definitions, operations, and an overview of some of their attributes, this study seeks to expand the hypersoft set idea to Pythagorean Neutrosophic Hypersoft Sets (PNHS). In this set structure two existing set structures are combined Pythagorean and Neutrosophic Hypersoft Sets theories with two dependent variables, Truthiness and Falsity, and one independent variable, Indeterminacy, with 0≤α*+β*≤ 2. Furthermore, an application is presented to show how a new judgment technique based on Pythagorean Neutrosophic Hypersoft Sets works. This study emphasizes the importance of PNHS in managing complicated and ambiguous information, enhancing our comprehension of and ability to use it in decision-making processes. Score functions are essential for evaluating the efficacy and dependability of the suggested approach, which helps make well-informed decisions and improves problem-solving skills across a range of fields.